Analisis Hukum Islam terhadap Uang Jujur (Jojokh) dalam Perkawinan Adat Lampung Pesisir - Hud Leo Perkasa Makki (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2017)
One of the marriage model in Lampung Pesisir custom is perkawinan jujur. This marriage is held with the money of jujur (jojokh) that the prospective groom gives to the family of the prospective bride before the marriage ceremony. Later when the ceremony was held, this money is not mentioned. In practice, the nominal jojokh money that the woman asks is sometimes very high. This paper examines how Islamic law views this kind of practice with ushul fiqh and fiqh reading tools. The result is that jojokh can be likened to a dowry in many aspects. Jojokh also qualifies' valid ‘urf. Related to how much jojokh is, Islamic law only set the minimum limit of dowry. While the maximum limit is not set. As long as it does not incriminate the prospective groom, no matter how nominal jojokh remains affirmed.